A zinc-based coordination polymer material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611350822.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-23
AI Technical Summary
此外,残留农药对水生生态系统微生物群落结构与功能亦造成不可逆干扰,进而影响整个水体生态安全
[0017](1)性能结构可调
Smart Images

Figure CN122958712A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coordination polymer materials technology, specifically to a zinc-based coordination polymer material, its preparation method, and its application. Background Technology
[0002] Pesticides, as key inputs for ensuring global food security and agricultural production, play an irreplaceable role in pest and disease control, increasing crop yields, and ensuring agricultural product supply. Statistics show that without pesticides, global crop yields would decrease by an average of 30%–50%, directly threatening the food supply for billions of people. However, with the increasing intensification of modern agriculture, pesticide application intensity has continued to rise, leading to long-term residues of pesticide active ingredients and their metabolites in soil, surface water, and groundwater. Particularly in developing countries, due to extensive application methods and lagging environmental management, pesticide residues widely enter the aquatic environment through rainwater runoff, surface runoff, and soil infiltration, forming persistent low-concentration pollution sources that are difficult to eliminate. Frequent incidents of pesticide residue exceeding standards in food (including grains, vegetables, and fruits) and drinking water have attracted significant international attention. Epidemiological and toxicological studies have confirmed that long-term low-dose exposure to pesticides such as benzimidazoles is closely related to endocrine disorders, neurodevelopmental toxicity, immunosuppression, and potential carcinogenic risks, posing a particular danger to sensitive populations (such as children and pregnant women). Furthermore, pesticide residues cause irreversible disruption to the structure and function of microbial communities in aquatic ecosystems, thereby affecting the overall ecological safety of aquatic bodies. Therefore, developing efficient, rapid, and easily regenerable adsorbent materials to effectively remove typical pesticide residues from the aquatic environment, thereby reducing human exposure pathways and ecological risks at the source, has become one of the key scientific issues urgently needing breakthroughs in the fields of environmental chemistry and materials science.
[0003] Among numerous candidate materials, metal-organic frameworks (MOFs), a class of crystalline porous hybrid materials formed by the self-assembly of metal ions (or metal clusters) and organic ligands through coordination bonds, have emerged as a standout in recent years, demonstrating unique advantages that traditional adsorbents cannot match. Their most prominent feature lies in the high degree of structural tunability: unlike traditional materials such as activated carbon and clay, which have fixed pore structures and randomly distributed functional groups, coordination polymers allow for "modular" construction at the molecular level. By systematically altering the electronic configuration of the metal center, the geometry of the ligands (length, bending angle, flexibility / rigidity), and synthesis conditions (temperature, solvent, template agent), the size, shape, polarity, and chemical microenvironment of the pores (such as hydrophobic regions and hydrogen bond donor / acceptor sites) can be customized with atomic-level precision. This precise controllability means that we can pre-design π-π stacking, polar functional groups, or uncoordinated carboxylic acid oxygen sites within the MOF pores, targeting the structural features of aromatic rings (π electron donors) and hydrogen bond donor / acceptor sites contained in pesticide molecules. Therefore, MOFs not only serve as structurally designable adsorption platforms, but also represent a "bottom-up" functional customization strategy—starting from the source of molecular recognition mechanisms to construct a safe adsorption material system with high selectivity and high capacity for specific pesticide pollutants, providing a novel solution for dealing with trace persistent organic pollutants in complex aquatic environments. Summary of the Invention
[0004] To address the aforementioned technical problems, the present invention aims to provide a method for preparing a zinc-based coordination polymer material, a second objective is to provide the zinc-based coordination polymer material thus prepared, and a third objective is to provide its applications. This is achieved through careful selection of Zn with specific coordination orientations. 2+ Ions serve as metal nodes and are combined with flexible polycarboxylic acid bridging ligands containing N heterocycles. By utilizing the directionality and predictability of coordination bonds, a three-dimensional framework structure with large-sized open rhombic channels and high guest and free regions is constructed, providing a transport channel with low diffusion barriers and enrichment and capture space for pesticide small molecules.
[0005] To achieve the first objective mentioned above, the present invention is implemented through the following technical solution: a method for preparing a zinc-based coordination polymer material, characterized by the following steps: 5–((4′–(imidazolium-1–yl)benzyl)oxy)isophthalic acid and zinc nitrate hexahydrate are dissolved in a mixed solvent of water and methanol, stirred at room temperature, and the mixed solution is transferred to a polytetrafluoroethylene reaction vessel and placed in a constant temperature oven for hydrothermal reaction to obtain pale yellow blocky crystals, and the pale yellow blocky crystals are ground into powder to obtain the zinc-based coordination polymer material.
[0006] This invention selects a flexible carboxylic acid ligand containing an aromatic ring and a nitrogen site as the structural unit, and proposes to use a mild hydrothermal synthesis method to comprehensively control factors such as reaction temperature, solvent system, metal salt type and pH value, and to design and synthesize a novel functionalized Zn-MOF to meet the adsorption requirements of carbendazim (CBZ) pesticide residues.
[0007] Zn with specific coordination orientation 2+ Ions, acting as metal nodes, are combined with flexible polycarboxylic acid bridging ligands containing N-containing heterocyclic rings. Utilizing the directionality and predictability of coordination bonds, a three-dimensional framework structure with large-sized open rhombic channels and a high guest accessibility region is constructed. This provides a low-diffusion-barrier transport channel and enrichment / capture space for pesticide small molecules, overcoming the technical bottleneck of traditional porous materials (such as microporous zeolites) having too small a pore size to effectively encapsulate CBZ molecules. When CBZ molecules enter the rhombic channels, they are first pre-enriched and oriented through π-π stacking and hydrogen bonding, followed by "locking" through coordination. Based on a "triple synergistic recognition mechanism"—the synergistic effect of coordination, hydrogen bonding, and π-π stacking—Zn-MOF possesses an effective adsorption capacity for CBZ.
[0008] In the above scheme: the molar ratio of 5–((4′–(imidazol-1–yl)benzyl)oxy)isophthalic acid and zinc nitrate hexahydrate is 0.1:(0.1-0.3), and the volume ratio of water to methanol in the mixed solution of water and methanol is 1:3-1:1.
[0009] Preferably, the molar ratio of 5–((4′–(imidazol-1–yl)benzyl)oxy)isophthalic acid and zinc nitrate hexahydrate is 0.1:0.3, and the volume ratio of water to methanol is 1:1.
[0010] To optimize single-crystal quality, the effect of the molar ratio of 5–((4′–(imidazolium-1–yl)benzyl)oxy)isophthalic acid to zinc nitrate hexahydrate on crystal growth was systematically investigated. When the reactant molar ratio was set to 0.1:0.1 and 0.1:0.2, insufficient zinc ions may lead to non-ideal coordination of ligands, resulting in varying degrees of lattice mismatch or visible cracks during crystal cooling or precipitation. Single-crystal X-ray diffraction results showed low data integrity and weak diffraction ability, indicating stress in crystal stacking or coordination modes under these conditions. In contrast, increasing the molar ratio to 0.1:0.3 promoted the formation of crack-free, smooth-surfaced, and highly crystalline crystals. The diffraction patterns of the crystals tested under this condition were clear, and the data integrity and signal-to-noise ratio met the requirements for refinement, contributing to the construction of a stable three-dimensional network structure.
[0011] In the above scheme: the hydrothermal reaction temperature is 85-160℃, and the hydrothermal reaction time is 72-96h;
[0012] After the reaction was complete, the mixture was allowed to cool naturally to room temperature, filtered, and washed with methanol and water to obtain pale yellow blocky crystals.
[0013] In the above method: the light yellow blocky crystals are placed in an agate mortar and ground for 20-30 minutes, and the particle size after grinding is 10-20µm.
[0014] A zinc-based coordination polymer material prepared by a method described above.
[0015] Application of the zinc-based coordination polymer material in the adsorption of carbendazim pesticide residues.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) Adjustable performance structure
[0018] This invention utilizes a Zn-MOF (Zn1) construction strategy based on flexible asymmetric dicarboxylic acid ligands, overcoming the structural limitations of symmetric rigid ligands. Existing MOFs mostly employ symmetric rigid carboxylic acid ligands (such as terephthalic acid and trimesic acid), which restricts the tunability of their channel shape and chemical microenvironment. This invention systematically utilizes flexible asymmetric dicarboxylic acid ligands (such as those constructed from different aromatic rings or nitrogen heterocycles, containing different substitution sites and freely rotating dihedral angles), whose coordination configuration uncertainty, partial rotational degrees of freedom, and asymmetric charge distribution, combined with Zn... 2+ Ions undergo controlled self-assembly. By adjusting the flexibility / rigidity ratio of ligands, the carboxyl spacing, and the degree of asymmetry, a novel Zn-MOF with non-centrosymmetric channels was successfully constructed, significantly improving the recognition of target molecules (CBZ) by the channels.
[0019] (2) Effectively removes pesticide molecules
[0020] This invention designs a "recyclable-in-situ regenerable" Zn-MOF adsorbent and establishes a structure-activity relationship model for the CBZ adsorption process. Immersion of Zn1 in a CBZ pesticide solution demonstrates significant and effective removal (q... e = 92.6 mg·L -1 Unlike most irreversible adsorption materials, this invention utilizes the moderate stability of the Zn–N / O coordination bond under neutral / weakly acidic conditions and the reversible conformational change of flexible ligands. This allows the material adsorbed with CBZ to achieve rapid regeneration at room temperature via elution with a simple solvent (such as an ethanol / water mixture), maintaining over 84% of the initial adsorption capacity after 5 cycles. A quantitative structure-activity relationship (QSAR) is established between the flexible ligand coordination mode, pore distribution, and adsorption performance, providing a theoretical basis for the subsequent design of Zn-MOFs for the targeted removal of benzimidazole pesticides. Attached Figure Description
[0021] Figure 1 The crystal structure diagram of the metal-organic framework Zn1 is shown in Figure 1. (a) Asymmetric structural unit; (b) Central metal Zn. 2+ Coordination polyhedron.
[0022] Figure 2 The dihedral angles of the ligands of the metal-organic framework Zn1 are: (a) the dihedral angle between two non-coplanar benzene rings, and (b) the dihedral angle between the benzene ring and the imidazole.
[0023] Figure 3 This is a two-dimensional layered structure diagram of the metal-organic framework Zn1.
[0024] Figure 4 This is a three-dimensional framework structure diagram of the metal-organic framework Zn1.
[0025] Figure 5 This represents the guest-accessible free region of the metal-organic framework Zn1.
[0026] Figure 6 The image shows the PXRD pattern of the metal-organic framework Zn1.
[0027] Figure 7 SEM and EDS images of the metal-organic framework Zn1.
[0028] Figure 8 The adsorption kinetics curves and pseudo-second-order model of Zn1 metal-organic framework for CBZ are shown in Figure 1. (a) Adsorption kinetic curves, (b) Pseudo-second-order model fitting data.
[0029] Figure 9 This is an internal diffusion model for the adsorption of CBZ by the metal-organic framework Zn1.
[0030] Figure 10 This represents the intraparticle diffusion of CBZ adsorbed by the metal-organic framework Zn1.
[0031] Figure 11 Research on the recyclability of metal-organic framework Zn1.
[0032] Figure 12 This is a schematic diagram of the adsorption mechanism. Detailed Implementation
[0033] The present invention will now be further described with reference to the accompanying drawings and embodiments.
[0034] Example 1
[0035] {Zn(ibia)} nSynthesis of (Zn1): 0.3 mmol Zn(NO3)2·6H2O and 0.1 mmol 5–((4′–(imidazol-1–yl)benzyl)oxy)isophthalic acid (H2ibia, purchased from Jinan Henghua Technology Co., Ltd.) were mixed and dissolved in a mixed solution of 4 mL MeOH and 4 mL H2O. The mixture was stirred at room temperature for 30 min. The solution was then placed in a 20 mL polytetrafluoroethylene (PTFE) reactor, sealed, and placed in a constant temperature oven at 120 °C for a hydrothermal reaction for 72 h. After cooling to room temperature, the mixture was filtered and washed with methanol and water to obtain pale yellow blocky crystals of Zn1 (yield: 71%, based on metal salt). The prepared crystal material was ground in an agate mortar for 20–30 min to obtain a powder with a particle size of 10–20 µm.
[0036] Subsequently, the molar ratio of 5–((4′–(imidazol-1–yl)benzyl)oxy)isophthalic acid and zinc nitrate hexahydrate was adjusted to 0.1:0.1 and 0.1:0.2 respectively to obtain different samples, and the single crystal structure of the samples was tested on the instrument.
[0037] When the molar ratio was 0.1:0.1 and 0.1:0.2, the resulting crystals developed cracks due to severe growth stress, leading to low integrity of single-crystal diffraction data and missing diffraction points, failing to meet the requirements for structural refinement. In contrast, when the molar ratio was increased to 0.1:0.3, the crystals exhibited good crystallinity, smooth surfaces, and no cracks, with complete diffraction data and excellent signal-to-noise ratio, providing the most reliable data for determining the precise coordination structure. The zinc-based coordination polymer material underwent X-ray single-crystal diffraction analysis, and the diffraction data was analyzed using Shelxt software. Using a single-crystal CIF file and Mercury (Hg) program version 3.0 software, simulated PXRD diffraction data of the zinc-based coordination polymer were exported. Within the diffraction angle range of 5° to 50°, the crystals exhibited sharp diffraction peaks, indicating that the experimentally synthesized crystals had excellent crystallinity. Furthermore, the positions of the experimentally measured main diffraction peaks were essentially the same as the simulated diffraction peaks, indicating that the prepared crystals had high phase purity, consistent with subsequent single-crystal analysis results.
[0038] The molar ratio of 5–((4′–(imidazol-1–yl)benzyl)oxy)isophthalic acid and zinc nitrate hexahydrate was fixed at 0.1:0.3, and the volume ratios of water and methanol were adjusted to 1:3 and 1:2 respectively (total volume 8 mL) to obtain single crystal samples. The single crystal structure of the samples was then tested.
[0039] When the water-to-methanol ratio in the mixed solvent was 1:2 and 1:3, the resulting crystals were small, and single-crystal X-ray diffraction results showed weak diffraction ability and poor data quality, making accurate structural analysis difficult. However, when the water-to-methanol ratio was adjusted to 1:1 (total volume 8 mL), uniform single crystals with clear crystal faces were obtained. Single-crystal X-ray diffraction analysis showed that this crystal had excellent diffraction ability, complete data collection, and good convergence of structural refinement, providing a reliable foundation for subsequent structural analysis and property discussion. Therefore, Zn1 was ultimately chosen for the experiment.
[0040] Metal-organic framework Zn1 crystalline single crystal structure, such as Figure 1-5 As shown, single-crystal X-ray diffraction analysis indicates that the metal-organic framework Zn1 crystallizes in the monoclinic crystal system, space group P 21 / c. The framework structure of Zn1 has not been reported in the literature; we analyzed its conformation, assembly mode, and overall packing structure. Due to the symmetry of the ligands, one asymmetric structural unit of Zn1 contains one Zn atom. 2+ Ions and 1 Hibia - Ligands. Crystallographically independent Zn 2+ The ion coordinates with three oxygen atoms (O1, O2, O3) to form a distorted planar quadrilateral geometry, where the three oxygen atoms O1, O2, and O3 all originate from partially protonated ligands. The adjacent Zn... 2+ Ions are bridged by carboxyl and nitrogen atoms in ligands to form one-dimensional metal chains along the b-axis. Subsequently, these one-dimensional chains are further connected by oxygen atoms on the same carboxyl group, expanding to form a two-dimensional planar grid layer. Finally, the partially deprotonated carboxyl groups on the ligands are assembled together to construct a three-dimensional framework.
[0041] A 1D rhomboid channel, measuring 2.774 × 2.047 nm, is present along the a-axis and could serve as a potential active binding group. Using the SQUEEZE subroutine in PLATON software, the structure factor of the electron density in the disordered solvent region was corrected, and its porosity was calculated to be 35.39%. It is reasonable to infer that the unique pore structure of the metal-organic framework Zn1 facilitates the reliable transport of small-molecule pesticide molecules, and its porous nature allows for the selective containment of small-molecule pesticide molecules in the environmental system.
[0042] Simulated PXRD diffraction data of the metal-organic framework Zn1 were exported using Mercury (Hg) program version 3.0 software. Figure 6 The diffraction peaks of the synthesized metal-organic framework were compared with those of the experimentally measured Zn1 metal-organic framework, and a high degree of match was found. This confirms that the synthesized metal-organic framework sample has high purity.
[0043] Scanning electron microscopy (SEM) can show ( Figure 7 The synthesized metal-organic framework Zn1 sample exhibits a blocky structure with a relatively smooth and flat surface. The sample is approximately 150 μm long. EDS elemental spectra show that each element is uniformly distributed within the metal-organic framework Zn1.
[0044] Example 2: Adsorption test of Zn1 on CBZ
[0045] All adsorption experiments were conducted in a constant-temperature shaker at 180 rpm and 25 °C.
[0046] First, pretreatment is performed by heating to 85°C in a vacuum oven to remove free solvent molecules from the Zn1 channels.
[0047] Add 40 mg of vacuum-dried material to a 40 mL solution of CBZ (concentration 50 mg·L⁻¹). -1 The supernatant was placed in a container and shaken at 25 °C for 21 h. After the adsorption experiment, 2 mL of the supernatant was taken with a pipette and its concentration was measured using a UV-Vis spectrophotometer. The residual amount of CBZ in the aqueous solution was recorded, and the adsorption capacity was calculated.
[0048] To better assess the adsorption capacity of Zn1 for CBZ, the adsorption kinetics and isotherms of CBZ were investigated. Figure 8 As shown, the adsorption capacity of CBZ increased rapidly after the addition of Zn1, and the adsorption of CBZ reached adsorption equilibrium at approximately 760 min (q). e = 92.6 mg·L -1 To evaluate the adsorption kinetics, pseudo-first-order and pseudo-second-order models were used to fit and analyze the corresponding data. The pseudo-first-order kinetic model (R1) was compared with the pseudo-first-order kinetic model. 2 Compared to the pseudo-second-order dynamics model (R² = 0.958), the R² value is significantly higher. 2 = 0.991) shows a better linear correlation. Utilizing this, the theoretical equilibrium adsorption amount calculated using the pseudo-second-order kinetic model is q. e = 93.1 mg·L -1 The results are closer to the experimental values. Clearly, the adsorption kinetics of CBZ by the metal-organic framework Zn1 better conforms to the pseudo-second-order model, indicating that chemisorption is the dominant adsorption process.
[0049] To elucidate the adsorption kinetics of CBZ on the metal-organic framework Zn1, the Weber-Morris model was used to quantitatively analyze the rate-controlling characteristics of diffusion behavior. The adsorption process exhibits a clear multi-stage nature, which can be summarized as three consecutive mass transfer stages: first, CBZ diffuses from the bulk solution to the liquid film on the outer surface of the adsorbent particles; then, CBZ molecules diffuse along the pore structure of the adsorbent into the internal binding sites of the particles; and finally, the adsorption dynamic equilibrium process controls the final stage. Figure 9 and Figure 10 According to the model fitting results, the straight lines corresponding to each stage did not pass through the origin. This phenomenon confirms that intraparticle diffusion is not the single rate-limiting step in the entire adsorption process, but rather jointly dominates the reaction rate along with liquid film diffusion, surface adsorption, and other stages. From a practical application perspective, Zn1 materials can be rapidly separated from the treated solution by sedimentation or filtration, completely avoiding the energy consumption and operational complexity of traditional centrifugal separation, thus laying a technological foundation for its future large-scale application in pesticide residue control.
[0050] In the commercial application of adsorption technology, studying the reusability of materials is crucial. The reusability of the metal-organic framework Zn1 was assessed after eluting with distilled water and ethanol to desorb contaminants. For example... Figure 11 As shown, after five repeated experiments, the reuse efficiency remained close to 84.08%, indicating that the prepared Zn1 could be an excellent candidate material for adsorbing CBZ. The reduced adsorption performance of Zn1 for CBZ may be due to the synergistic effect of irreversible occupation of chemical sites, pore blockage, and loss of active components.
[0051] like Figure 2 As shown, the adsorption of CBZ by the metal-organic framework Zn1 is attributed to its unique framework structure, coordination, π···π interactions and hydrogen bonding, due to the open metal sites of Zn1 and the presence of aromatic rings, imidazoles, carbonyl groups and ester groups of CBZ.
[0052] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a zinc-based coordination polymer material, characterized in that, The following steps were followed to prepare the zinc-based coordination polymer material: 5–((4′–(imidazol-1–yl)benzyl)oxy)isophthalic acid and zinc nitrate hexahydrate were dissolved in a mixed solvent of water and methanol and stirred at room temperature. The mixed solution was then transferred to a polytetrafluoroethylene reactor and placed in a constant temperature oven for hydrothermal reaction to obtain pale yellow blocky crystals. The pale yellow blocky crystals were then ground into powder to obtain the zinc-based coordination polymer material.
2. The method for preparing the zinc-based coordination polymer material according to claim 1, characterized in that: The molar ratio of 5–((4′–(imidazol-1–yl)benzyl)oxy)isophthalic acid and zinc nitrate hexahydrate is 0.1:(0.1-0.3), and the volume ratio of water to methanol in the mixed solution of water and methanol is 1:3-1:
1.
3. The method for preparing the zinc-based coordination polymer material according to claim 2, characterized in that: The molar ratio of 5–((4′–(imidazol-1–yl)benzyl)oxy)isophthalic acid and zinc nitrate hexahydrate is 0.1:0.3, and the volume ratio of water to methanol is 1:
1.
4. The method for preparing the zinc-based coordination polymer material according to claim 3, characterized in that: The hydrothermal reaction temperature is 85-160℃, and the hydrothermal reaction time is 72-96h; After the reaction was complete, the mixture was allowed to cool naturally to room temperature, filtered, and washed with methanol and water to obtain pale yellow blocky crystals.
5. The method for preparing the zinc-based coordination polymer material according to any one of claims 1-4, characterized in that: The pale yellow blocky crystals were ground in an agate mortar for 20-30 minutes, resulting in a particle size of 10-20µm.
6. A zinc-based coordination polymer material prepared by the method of any one of claims 1-5.
7. The application of the zinc-based coordination polymer material according to claim 6 in the adsorption of carbendazim pesticide residues.